1975
DOI: 10.1021/bi00693a031
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of human serum albumin by p-nitrophenyl acetate

Abstract: Human serum albumin reacts very rapidly with p-nitrophenyl acetate (NphOAc). Rapid acetylation of the protein accompanies and largely accounts for the easily observed rapid formation of of p-nitrophenolate ion. One group is acetylated much faster than all others. It appears to be located in a high affinity binding site for small fatty acid anions, to have a pKa of 8.7, and a limiting bimolecular rate of reaction with NphOAc of approximately 3 X 10(4) M-1 sec-1 at alkaline pH values. Rapid reversible binding ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 13 publications
(15 reference statements)
10
111
0
Order By: Relevance
“…It is concluded that the rate of formation of the acylated albumin adduct is fast (k 2 ), and that the slow step in hydrolysis of the p-NPA ester is deacylation (k 3 ). This provides direct evidence that deacylation is the rate-limiting step (k 3 , k 2 ) in albumin-catalyzed hydrolysis of p-NPA, confirming results obtained from burst kinetics [2]. The reaction of o-NTFNAC with albumin rapidly produced a yellow color (o-nitroaniline), demonstrating that the acetanilide substrate was being hydrolyzed.…”
Section: Maldi-tofsupporting
confidence: 83%
See 1 more Smart Citation
“…It is concluded that the rate of formation of the acylated albumin adduct is fast (k 2 ), and that the slow step in hydrolysis of the p-NPA ester is deacylation (k 3 ). This provides direct evidence that deacylation is the rate-limiting step (k 3 , k 2 ) in albumin-catalyzed hydrolysis of p-NPA, confirming results obtained from burst kinetics [2]. The reaction of o-NTFNAC with albumin rapidly produced a yellow color (o-nitroaniline), demonstrating that the acetanilide substrate was being hydrolyzed.…”
Section: Maldi-tofsupporting
confidence: 83%
“…Albumin is capable of binding numerous compounds and displays several enzymatic activities [1], including esterase activity with p-nitrophenyl acetate and other aryl-esters, including drugs and prodrugs [2][3][4]. The esteratic site of human albumin was found to be the binding site for several drugs, organophosphates and fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, data here reported indicate that the deacylation process is rate limiting in the HSA-catalyzed hydrolysis of NphOAc (i.e., k +3 << k +2 ). Lastly, values of K s and k +2 here obtained are in agreement with those previously reported [12,13].…”
supporting
confidence: 92%
“…HSA (from Sigma-Aldrich, St. Louis, MO, USA) was essentially fatty acid free, according to the charcoal delipidation protocol [9][10][11] .0°C, were analyzed in the framework of the minimum three step-mechanism reported in Scheme 1 [8,[12][13][14][15], where HSA is the substrate-free protein, NphOAc is the substrate, HSA:NphOAc is the reversible protein-substrate complex, HSA-OAc is considered to be an ester formed between the acyl moiety of the substrate and the O atom of the Tyr411 phenoxyl group [8], AcOH is acetic acid, k +l is the second-order rate constant for the formation of the HSA:NphOAc complex starting from HSA and NphOAc, k À1 is the first-order rate constant for the dissociation of the HSA:NphOAc complex to HSA and NphOAc, K s (=k À1 /k +1 ) is the pre-equilibrium constant, k +2 is the first-order acylation rate constant, k À2 is the first-order rate constant for the conversion of HSA-OAc to HSA:NphOAc, k +3 is the first-order deacylation rate constant, and k À3 is the second-order rate constant for the formation of the HSA-OAc adduct starting from HSA and AcOH.…”
Section: Hsamentioning
confidence: 99%
“…Thermocoagulation removes contaminating proteins such as nucleases and proteases; however, prolonged exposure to heat can cause BSA molecules to form hydrophobic aggregates which may not revert to monomers upon cooling [16][17][18][19][20]. In some preparations, nucleases are inactivated by acetylation using chemical agents such as p-nitrophenyl acetate [21,22]. Acetylation of tyrosine residues in BSA limits its laboratory use by interfering with color development in assays such as the Lowry's.…”
Section: Introductionmentioning
confidence: 99%